Time series modelling spatiotemporal changes in Biogeoclimatic ecosystem classification (BEC) zones between 1997 and 2019 in West-Central British Columbia, Canada - Ilythia D. Morley; Kevin Hanna; Chris T. Darimont; Mathieu L. Bourbonnais; Ilythia D. Morley (Ecological Informatics)
Understanding the spatial extent and temporal variability of ecosystem processes is essential for contextualizing land use and land cover change due to disturbance. In this study, we apply an advanced time series modelling method to assess and map ecosystem change and characterize ecosystem cover in west-central British Columbia, Canada. We couple Biogeoclimatic Ecosystem Classification (BEC) zone data with metrics derived from Landsat imagery to model how biogeoclimatic ecosystem cover, interpreted as an indicator of shifting vegetation seasonality, varies over a broad spatiotemporal scale. To do so, we apply the Time-Weighted Dynamic Time Warping (TWDTW) time series modelling approach by relating the spectral characteristics of Landsat data and derived indices from 1997 to 2019. Results highlight important transitions between biogeoclimatic ecosystem classes, with a transition of the interior Douglas-fir Dry to the montane-spruce Dry and the Sub-Boreal Pine to the Spruce zone Dry zones in response to large wildfires in 2003 and 2009. The assessment of ecosystem change across broad spatial and temporal scales is important for assessing the cumulative impacts of changes across highly variable landscapes on essential landscape services.